Italian immigrant radical culture : the idealism of the sovversivi in the United States, 1890-1940 - Bencivenni, Marcella (New York University Press, 2011)
Maligned by modern media and often stereotyped, Italian Americans possess a vibrant, if largely forgotten, radical past. In Italian Immigrant Radical Culture, Marcella Bencivenni delves into the history of the sovversivi, a transnational generation of social rebels, and offers a fascinating portrait of their political struggle as well as their milieu, beliefs, and artistic creativity in the United States. As early as 1882, the sovversivi founded a socialist club in Brooklyn. Radical organizations then multiplied and spread across the country, from large urban cities to smaller industrial mini.